Data from: Validating the incorporation of 13C and 15N in a shorebird that consumes an isotopically distinct chemosymbiotic bivalve - Van Gils, Jan A.; Ahmedou Salem, Mohamed Vall (Data Archiving and Networked Services (DANS), 2016)
The wealth of field studies using stable isotopes to make inferences about animal diets require controlled validation experiments to make proper interpretations. Despite several pleas in the literature for such experiments, validation studies are still lagging behind, notably in consumers dwelling in chemosynthesis-based ecosystems. In this paper we present such a validation experiment for the incorporation of 13C and 15N in the blood plasma of a medium-sized shorebird, the red knot (Calidris canutus canutus), consuming a chemosymbiotic lucinid bivalve (Loripes lucinalis). Because this bivalve forms a symbiosis with chemoautotrophic sulphide-oxidizing bacteria living inside its gill, the bivalve is isotopically distinct from ‘normal’ bivalves whose food has a photosynthetic basis. Here we experimentally tested the hypothesis that isotope discrimination and incorporation dynamics are different when consuming such chemosynthesis-based prey. The experiment showed that neither the isotopic discrimination factor, nor isotopic turnover time, differed between birds consuming the chemosymbiotic lucinid and a control group consuming a photosynthesis-based bivalve. This was true for 13C as well as for 15N. However, in both groups the 15N discrimination factor was much higher than expected, which probably had to do with the birds losing body mass over the course of the experiment. Body_massesBody masses of the experimental birdsBleeding_sessionsDates of the collection of the blood samplesDiet_per_IDDiet (prey species) offered per individual birdIsotope_ratiosStable isotope ratios in blood cells and plasma per bird per bleeding session.